Paleogenetic approaches in tsunami deposit studies - Engel, Max; Schön, Isa; Patel, Tasnim; Pawlowski, Jan; Szczuciński, Witold; Dawson, Sue; Garrett, Ed; Heyvaert, Vanessa M. A. (Geological records of tsunamis and other extreme waves, 2020)
In search of new proxies to improve tsunami deposit identification, ancient DNA (aDNA) has recently started to be used to characterize microbial communities or microfossil assemblages. For instance, foraminifera aDNA can be used when carbonate tests have been dissolved after deposition to still trace the source area of a deposit and to discriminate it from other coastal facies. Even though DNA is prone to quick degradation, it may preserve in sediments for up to tens of thousands of years; here, it is referred to as sediment ancient DNA (sedaDNA) or environmental DNA (eDNA), which also includes recent DNA. sedaDNA can be targeted through high-throughput amplicon sequencing (metabarcoding). First studies show that microbial communities differ in known storm and tsunami deposits at statistically significant levels and that marine foraminiferal assemblages can be reconstructed in late Holocene onshore tsunami deposits, indicating that sedaDNA can be a meaningful addition to the multi-proxy toolkit used in paleotsunami research in the future.
Gesehen am 18.05.2021